Anthracycline-based chemotherapy in early breast cancer: Correlation with receptor status (estrogen, progesterone and human epidermal growth factor-2 - Ahmed Abdelhamed Elsayed Oda; Ahmed Abdelmabood Zeeneldin; Amani Mohamed Helal; Rabab Mohamed Gaafar (Cairo : Ahmed Abdelhamed Elsayed Oda, 2010)
Breast cancer (BC) is a heterogeneous disease that encompasses several distinct entities with different biological characteristics and clinical behavior. The purpose of this study is to correlate between the outcome of early breast cancer patients who received anthracycline-based chemotherapy with the tumor receptor status namely estrogen, progesterone and HER-2 receptor as regard disease free survival and overall survival
Thesis (M.Sc.) - Cairo University - National Cancer Institute - Department of Oncology-Medical
Issued also as CD
Keywords: Anthracyclines; Breast cancer; Estrogen receptor